Does A Contract Strategy Play A Role In Improving The Performance Delivery Of An Oil And Gas Project In Oman? - et. al., Ahmed Salim Al Saeedi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Oil and gas projects suffer from time-overrun worldwide and Oman is no different. Such Delays lead projects to miss their targets of schedule and budget which affect the country economy. One of the possible causes of time overrun is the contract strategy adopted in those projects. This paper presents empirical data to show which strategy is more likely to causes the projects miss its schedule target. Semi-Structured interviews have been conducted to increase the confidence of the results. This study revealed that more than 60% the respondents have expressed that EP+C contract strategy is the strategy that is more likely to have projects miss their main targets. Also contract strategy factor has been ranked high important factor that causes time overrun in oil and gas projects. In addition, a questionnaire was made to evaluate the oil and gas projects that have completed on agreed schedule, and it showed that 80% of respondents have revealed such projects have a contract strategy of EPC.